Hedging of currency risks in the conditions of devaluation on IFRS - Beysenbaeva, A. K. (Journal of Economic Research & Business Administration, 2016)
Formation of market economy in our country devaluation of national currency and the increasing potential for strengthening of pressure upon tenge, instruments of hedging of currency risks remain unclaimed. Also in article are considered an order of the organization of the accounting of hedging in the conditions of inflation and to use in practice of bank activity, recommendations to develop necessary action are made.